Biological carbon dioxide sequestration potential of Bacillus pumilus - Komala, T.; Tan., C. Khun (Universiti Kebangsaan Malaysia, 2014)
Bacillus pumilis was isolated and identified from limestone and the ability towards carbon dioxide (CO2) sequestration was demonstrated. B. pumilus (S3 SC_1), isolated from Gua Tempurung, Gopeng, Perak was able to form calcite in the presence of calcium ions. B. pumilus was successfully characterized by using conventional biochemical characterization and 16s rDNA sequencing. Three types of experimental systems with B. pumilus, without B. pumilus and without continuous supply of CO2 with the presence of B. pumilus which could produce extracellular carbonic were studied to determine the effects of bacterially produced carbonic anhydrase (CA) by B. pumilus in removing CO2 as calcite. Through our current study, CO2 sequestration ability of B. pumilus was proven.